The Philippines as tool-forged nation revisiting Nick Joaquin’s use of Marshall McLuhan’s Medium Theory to reconstruct colonial history - Labiste, Ma. Diosa (2024)
Access online through this link: https://www.plarideljournal.org/article/the-philippines-as-tool-forged-nation-revisiting-nick-joaquins-use-of-marshall-mcluhans-medium-theory-to-reconstruct-colonial-history
Keywords: Joaquin, Nick, 1917-2004; McLuhan, Marshall; Imperialism; Imperialism and history